PROFIL PEMECAHAN MASALAH MATEMATIKA SISWA SMK KELAS X DITINJAU DARI GAYA KOGNITIF - Arfanuddin, Arfanuddin; Sukayasa, Sukayasa; Rochaminah, Sutji (AKSIOMA : Jurnal Pendidikan Matematika, 2016)
Abstract: This paper aims to describe the mathematic problem solving profile of 10th class SMK students from both Field Independent (FI) and Field Dependent (FD) Cognitive Style. This is a descriptive research by qualitative approach. For classifying the cognitive style of students, it used Group Embedded Figures Test (GEFT). The data collection technic are giving mathematical problem, depth interview, and observation through four steps problem solving based on Polyaâs view, those are (a) understanding problem, (b) arranging plan, (c), doing plan, and (d) verification. The results show that: (1) the FI mathematic problem solving profile, in terms of understanding problem are: logically and clearly able to identify and analyze the problem, while FD is logically and clearly able to identify the problem, (2) FI and FD in terms of arranging plan is able to arrange the solution plan strategy to solve the problem, (3) FI and FD have differences in terms of doing plan, those are: FI is systematically able to employ the problem solving strategy planned, while FD is able to employ the problem solving strategy nevertheless unsystematically, (4) FI and FD simultaneously verify the answer and the gained results by tracing the calculation of results created, and what is more that FI employs the constructed formulation for verifying the answer.Keywords: Problem Solving, Cognitive Style